Determination of expected time to recruitment in manpower planning - R. Vinoth, S. Parthasarathy (Recent Research in Science and Technology, 2009)
Manpower planning in a sense, according to Barthlomew [1], is concerned with matching the supply of people with the jobs available. Recruitment is required to compensate the wastage of manpower; wastage refers to the loss of manpower in the organization. Recruitment cannot be made frequently since it involves cost. The threshold level is the maximum amount of wastage that can be permitted in the organization beyond which the organization reaches a point of breakdown. It is similar to the concept of shock model and cumulative damage discussed by Esary et al. [2]. In this paper we made an attempt to determine the expected time to recruitment, assuming that the threshold as exponentiated exponential distribution which introduced by Gupta and Kundu [3].